Diencephalic syndrome: a frequently neglected cause of failure to thrive in infants - Ahlee Kim; Jin Soo Moon; Hye Ran Yang; Ju Young Chang; Jae Sung Ko; Jeong Kee Seo (Korean Pediatric Society, 2015)
PurposeDiencephalic syndrome is an uncommon cause of failure to thrive in early childhood that is associated with central nervous system neoplasms in the hypothalamic-optic chiasmatic region. It is characterized by complex signs and symptoms related to hypothalamic dysfunction; such nonspecific clinical features may delay diagnosis of the brain tumor. In this study, we analyzed a series of cases in order to define characteristic features of diencephalic syndrome.MethodsWe performed a retrospective study of 8 patients with diencephalic syndrome (age, 5-38 months). All cases had presented to Seoul National University Children's Hospital between 1995 and 2013, with the chief complaint of poor weight gain.ResultsDiencephalic syndrome with central nervous system (CNS) neoplasm was identified in 8 patients. The mean age at which symptoms were noted was 18±10.5 months, and diagnosis after symptom onset was made at the mean age of 11±9.7 months. The mean z score was -3.15±1.14 for weight, -0.12±1.05 for height, 1.01±1.58 for head circumference, and -1.76±1.97 for weight-for-height. Clinical features included failure to thrive (n=8), hydrocephalus (n=5), recurrent vomiting (n=5), strabismus (n=2), developmental delay (n=2), hyperactivity (n=1), nystagmus (n=1), and diarrhea (n=1). On follow-up evaluation, 3 patients showed improvement and remained in stable remission, 2 patients were still receiving chemotherapy, and 3 patients were discharged for palliative care.ConclusionDiencephalic syndrome is a rare cause of failure to thrive, and diagnosis is frequently delayed. Thus, it is important to consider the possibility of a CNS neoplasm as a cause of failure to thrive and to ensure early diagnosis.